Follow up after spontaneous coronary artery dissection: a report of five cases. Issue 2 (February 1996) - Zampieri, P.; Aggio, S.; Roncon, L.; Rinuncini, M.; Canova, C.; Zanazzi, G.; Fiorencis, R.; Zonzin, P.
Abstract : Five cases of spontaneous coronary artery dissection (SCAD) are reported, three in women and two in men (mean age 44 years; range 28-65), all of whom suffered a myocardial infarction. Common risk factors for coronary artery disease were present in the two men; in the female group one patient was taking an oral contraceptive, one was in the postpartum period, and the third was a smoker. Only the three women received intravenous alteplase and their ejection fraction was normal; both men had impaired left ventricular function. Two patients had SCAD of the left anterior descending coronary artery and three of the right coronary artery. Only the two men had angiographic features of coronary atherosclerotic involvement. No patients required surgical revascularisation or percutaneous transluminal coronary angioplasty. At a mean follow up of 27 months (range 6 to 40) all patients were alive and all but one were asymptomatic.